Architectures of hurry mobilities, cities and modernity - Mackintosh, Phillip Gordon 1960-; Dennis, Richard 1949-; Holdsworth, Deryck 1947- (Routledge, 2018)
"'Hurry' is an intrinsic component of modernity. It exists not only in tandem with modern constructions of mobility, speed, rhythm, and time-space compression, but also with infrastructures, technologies, practices, and emotions associated with the experience of the 'mobilizing modern'. 'Hurry' is not simply speed. It may result in congestion, slowing-down or inaction in the face of over-stimulus. Speeding-up is often competitive: faster traffic on better roads made it harder for pedestrians to cross, or for horse-drawn vehicles and cyclists to share the carriageway with motorised vehicles. Focussing on the cultural and material manifestations of 'hurry', the book's contributors analyse the complexities, tensions and contradictions inherent in the impulse to higher rates of circulation in modernizing cities. The collection includes but also goes beyond accounts of new forms of mobility (bicycles, buses, underground trains) and infrastructure (street layouts and surfaces, business exchanges, and hotels) to show how modernity's 'architectures of hurry' have been experienced, represented, and practised since the mid-nineteenth century. Ten case studies explore different expressions of 'hurry' across cities and urban regions in Asia, Europe, and North and South America, while substantial introductory and concluding chapters situate 'hurry' in the wider context of modernity and mobility studies and reflect on the future of 'hurry' in an ever-accelerating world.This diverse collection will be relevant to researchers, scholars and practitioners in the fields of planning, cultural and historical geography, urban history and urban sociology."--Provided by publisher
Keywords: City and town life; Sociology, Urban; City planning